Performance Evaluation of Elite Durum Wheat Genotypes for Yield and Stem Rust Response - Ishetu, Yewubdar Shewaye; Homa, Shitaye; Batu, Worknesh (Discoveries in Agriculture and Food Sciences, 2023)
Durum wheat is one of the most important crops worldwide and Ethiopia is the major producer in sub-Saharan Africa (SSA). However, there is a huge gap between domestic production and demand in Ethiopia. Hence, getting high yielder with resistant for multiple races of rusts especially for stem rust became challenging. This could be due to limited availability of resistance to multiple stem rust races coupled with the rapid occurrence and spread of virulent races of stem rust. Hence, objective of this study is to identify high yielding and stem rust resistant genotypes and use them as parents in the breeding program and advance to national variety trial to select for wide adaptability. Sixty advanced genotypes were evaluated across three locations during 2020/21 cropping season. The trial was set up using row-column design in two replications. Data on grain yield, yield related traits and stem rust were collected. Stem rust was scored following the modified Cobb’s scale. Under high disease pressure the genotypes showed disease response and severity variations from RMR to S and from 5% to 100%, respectively indicating the presenece of variation for stem rust response. There were also genotypes which showed suceptable reaction and high grain yield and yield related traits. Hence, this may be due to minor gene resistance to stem rust. Generally, about 13 genotypes had good grian yield, thousand kernel weight and stem rust resistance. We can recommend these genotypes to test across country for their wide adaptability and as a parents for crossing.